PI3Kδ activates E2F1 synthesis in response to mRNA translation stress - Gnanasundram, Sivakumar Vadivel; Pyndiah, Slovénie; Daskalogianni, Chrysoula; Armfield, Kate; Nylander, Karin; Wilson, Joanna B; Fåhraeus, Robin (Nature communications, 2017)
The c-myc oncogene stimulates ribosomal biogenesis and protein synthesis to promote cellular growth. However, the pathway by which cells sense and restore dysfunctional mRNA translation and how this is linked to cell proliferation and growth is not known. We here show that mRNA translation stress in cis triggered by the gly-ala repeat sequence of Epstein-Barr virus (EBV)-encoded EBNA1, results in PI3Kδ-dependent induction of E2F1 mRNA translation with the consequent activation of c-Myc and cell proliferation. Treatment with a specific PI3Kδ inhibitor Idelalisib (CAL-101) suppresses E2F1 and c-Myc levels and causes cell death in EBNA1-induced B cell lymphomas. Suppression of PI3Kδ prevents E2F1 activation also in non-EBV-infected cells. These data illustrate an mRNA translation stress-response pathway for E2F1 activation that is exploited by EBV to promote cell growth and proliferation, offering new strategies to treat EBV-carrying cancers.
Keywords: buněčné linie; fosfatidylinositol-3-kinasy třídy I; myši; Cell Proliferation; Neoplasms; Protein Biosynthesis; Gene Expression Regulation, Neoplastic; nádorové buněčné linie; Epstein-Barr Virus Nuclear Antigens; Cell Line, Tumor; Class I Phosphatidylinositol 3-Kinases; lidé; Humans; Host-Pathogen Interactions; Herpesvirus 4, Human; Mice; Animals; proliferace buněk; zvířata; nádory; proteosyntéza; E2F1 Transcription Factor; virus Epsteinův-Barrové; interakce hostitele a patogenu; messenger RNA; transkripční faktor E2F1; regulace genové exprese u nádorů; Cell Line; virus Epsteinův-Barrové - jaderné antigeny; RNA, Messenger